(untitled) (AYUSHDHARA, 2021)
Diabetes mellitus is a metabolic disorder causing hyperglycaemia with defect in metabolism of carbohydrates, fats, and proteins due to defect in insulin secretion, or its utilization or both. Prediabetes is a condition in which the blood glucose levels do not meet the criteria for diabetes or too high to be considered normal (ADA). It is an early stage of DM. So it is important to diagnose Diabetes Mellitus type 2 in the previous stage that is prediabetes. It is already in practice to diagnose it with laboratory blood tests. But additionally, we can also take help of Prameha purvarupas as premonitory symptoms in patients prediabetes. HbA1C is a useful parameter to diagnose prediabetes. There is mild or no symptoms mentioned for prediabetes. Purvarupas of Prameha mentioned in Ayurvedic samhitas can be useful to know early stage of Diabetes mellitus type 2, clinically. The purpose of this article is to highlight the importance of Purvarupa of Prameha to diagnose prediabetes. So, the need of hour is to focus on screening and diagnosing pre-Diabetes earlier, by spreading knowledge and awareness among society which will play a key role to reduce the conversion of pre-diabetes to diabetes mellitus.